(untitled) (Gestión y Gerencia, 2018)
The objective of this research is to describe distance education in virtual learning environments at the Lisandro Alvarado Centroccidental University (UCLA), School of Economics and Business Sciences (DCEE), under the blended modality, taking the experiences in the subjects Public Administration I and Electiva II-Family Businesses. The research is qualitative, descriptive, interpretive and documentary, considering that human activities and their relationships are centered on information and knowledge, based on information and communication technologies (TIC). This reality requires institutions of higher education, flexibility of its procedures and administrative structure to adapt to new forms of training more in line with the needs that this new information society presents. UCLA, in response to new global educational trends, has been making adjustments and updates that involve the inclusion of virtual learning environments as tools for the construction of knowledge. As conclusions, UCLA, specifically the DCEE, maintains a process of continuous training, motivational to teachers, in order to increase the supply of subjects under this modality, which has a positive impact on the academic achievements of students